ANALISIS PERTIMBANGAN HUKUM HAKIM PENGADILAN NEGERI MEMPAWAH TERHADAP PENGABULAN GUGATAN REKONVENSI PUTUSAN NOMOR 46/Pdt.G/2020/PN MpwTENTANG SENGKETA TANAH - NIM. A1011201193, ABANG BIMA AL MALIK ABDUL HAFIIDZ WAHYUD (Jurnal Fatwa Hukum, 2024)
Abstract Land registration really determines that humans and land have a legal relationship as permanent objects. Disputes regarding land ownership still occur frequently, even though land registration has been carried out and strong evidence in the form of land title certificates, it is proven that from year to year land disputes continue to increase. This research will discuss the legal considerations of the judge who granted the reconvention lawsuit related to Decision Number 46/Pdt.G/2020/Pn Mpw regarding land disputes. This research aims to find out and analyze the judge's legal considerations, as well as the legal consequences of granting the reconvention lawsuit in Decision Number 46/Pdt.G/2020/Pn Mpw.Using normative legal research methods, the author collects data through document study and literature study. The data obtained was then analyzed descriptively qualitatively which will be discussed descriptively in the research results and discussion later. The result of this research is that the judge granted the issuance of land tittle deed in the name of Ivan Widarko, which was issued according to legal procedures by the previous owner. The Reconvention Plaintiff legally purchased the land before the Land Deed Official and registered it with the National Land Agency. The judge assessed the Rekonvention Plaintiff as a buyer in good faith and stated that land tittle deed number . 380/Kuala Dua is valid. This decision fulfills the principles of expediency, justice and legal certainty, providing protection and recognition of Ivan the Reconvention Plaintiff's property rights. The decision of the Panel of Judges provides legal certainty to Ivan Widarko as the legal owner of land tittle deed No. 380/Kuala Dua, ensuring that their rights are recognized and protected, as well as giving them full rights to manage or sell the land without worry of disputes. For the Rekonvention Defendant, this decision means losing his claim to the land and no longer being able to claim ownership. Reconvention Defendants may also have to bear legal and court costs incurred during the litigation process. Keywords: Judge's Legal Considerations, Land Dispute, Reconvention Lawsuit Abstrak Pendaftaran tanah sangat menetukan bahwa manusia dengan tanah mempunyai hubungan hukum sebagai benda tetap. Sengketa tentang kepemilikan tanah masih sering terjadi, meskipun telah dilakukan pendaftaran tanah dan bukti yang kuat berupa berupa sertifikat hak atas tanah, ini terbukti dari tahun ke tahun sengketa tanah terus mengalami peningkatan. Penelitian ini akan membahas tentang pertimbangan hukum hakim yang mengabulkan gugatan rekonvensi terkait Putusan Nomor 46/Pdt.G/2020/Pn Mpw tentang sengketa tanah. Penelitian ini bertujuan untuk mengetahui dan menganalisis pertimbangan hukum hakim, serta akibat hukum atas dikabulkannya gugatan rekonvensi dalam Putusan Nomor 46/Pdt.G/2020/Pn Mpw.Dengan metode penelitian hukum normatif, penulis mengumpulkan data melalui studi dokumen dan studi kepustakaan. Data yang didapat kemudian dianalisis secara deskriptif kualitatif yang akan membahas secara deskriptif dalam hasil penelitian dan pembahasan nantinyaHasil dari penelitian ini adalah Hakim mengabulkan penerbitan Sertifikat Hak Milik (SHM) atas nama Ivan Widarko, yang diterbitkan sesuai prosedur hukum oleh pemilik sebelumnya. Penggugat Rekonvensi membeli tanah tersebut secara sah di hadapan Pejabat Pembuat Akta Tanah (PPAT) dan mendaftarkannya ke Badan Pertanahan Nasional (BPN). Hakim menilai Penggugat Rekonvensi sebagai pembeli beritikad baik dan menyatakan SHM No. 380/Kuala Dua sah. Keputusan ini memenuhi asas kemanfaatan, keadilan, dan kepastian hukum, memberikan perlindungan dan pengakuan atas hak milik Ivan Penggugat Rekonvensi. Keputusan Majelis Hakim memberikan kepastian hukum kepada Ivan Widarko sebagai pemilik sah SHM No. 380/Kuala Dua, memastikan hak-haknya diakui dan dilindungi, serta memberikan hak penuh untuk mengelola atau menjual tanah tersebut tanpa khawatir sengketa. Bagi Tergugat Rekonvensi, keputusan ini berarti kehilangan klaim atas tanah dan tidak dapat lagi menuntut kepemilikannya. Tergugat Rekonvensi juga mungkin harus menanggung biaya hukum dan pengadilan yang timbul selama proses litigasiKata Kunci: Pertimbangan Hukum Hakim, Sengketa Pertanahan, Gugatan Rekonvensi